EFFECT OF SERVICE QUALITY WORD OF MOUTH WITH MEDIATION PATIENT SATISFACTION AND MODERATED PRICE - Handini, Satiti; Ruswanti, Endang (Aktualita Manajemen, 2016)
AbstractThis study examines the relationship between service quality, pricing, satisfaction and word of mouth (WOM) patients in the house of bouty and healthy Women Hauraa. The more specific objectives of this study is: determine the effect of service quality on patient satisfaction, determine the effect of price on patient satisfaction, determine the effect of patient satisfaction with word of mouth: determine the effect of service quality to WOM. Respondents in this study were 170 respondents with criteria have at least high school education, aged between 17-60 years old and female. Sample determination using purposive sampling method. This study uses analysis Structural Equation Modelling with application software version 8.8 lisrel. The results showed that: Quality of service, significant effect on patient satisfaction, Â The price does not have a significant influence on patient satisfaction, patient satisfaction significant effect on word of mouth and Quality of service does not have a significant influence on WOM. The results provide a practical contribution that the management house of bouty and healthy Women Hauraa should be emphasized that reliability, responsiveness, tangibles, assurance and empathy is maintained, because five dimensions have considerable influence on the satisfaction of patients that will create WOM. WOM plays a role important enough in terms of marketing house of bouty and healthy Women Hauraa. Contributions from the results of this study can be used as a reference by the management to improve service quality performance.Keywords: service quality, patient satisfaction, price, word of mouth, a beauty clinic